Previous unilateral inguinal hernia repair increase risk of new developed inguinal hernia: a nationwide Longitudinal Cohort Study in Asian male adult patients - Tseng, Shih-I.; Li, Ching-Chia; Lee, Hsiang-Ying; Chen, Jian-Han (Surgical endoscopy, 2022)
Introduction Our study aims to identify that patients who received hernia repair previously did have higher risk of occurrence of newly developed inguinal hernia, named as a contralateral inguinal hernia (CIH), than patients who never received inguinal hernia surgery before. Materials and methods We collected data from the National Health Insurance Research Database (NHIRD) of Taiwan retrospectively. In the study cohort, 64,089 Asian male adults who underwent primary unilateral inguinal hernia repair during 2003–2008 were included using ICD-9 diagnostic and surgical codes. Another 64,089 male adults without hernia repair history were included as control group via propensity score match. Results The median follow-up period is 93.53 months. After multivariate analysis, the risk of newly developed inguinal hernia in unilateral inguinal hernia (UIH) repair cohort was significantly higher (adjusted HR 6.364, 95% CI 6.012–6.737, P < 0.001) than the control group. In subgroup analysis, patients without mesh repair (adjusted HR 6.706, P < 0.001) and patients with mesh repair (adjusted HR 5.559, P < 0.001) both showed higher risk of developing newly developed inguinal hernia which needs repair. Conclusions Asian men with UIH repair history had a higher risk of developing new inguinal hernia at the contralateral site, namely CIH, than the general population. The surgeon should inform the possibility of CIH after initial herniorrhaphy, therefore, monitoring the occurrence of CIH is necessary.